Effects of Vertical Transmission of Respiratory Viruses to the Offspring - Manti, Sara; Leonardi, Salvatore; Rezaee, Fariba; Harford, Terri J.; Perez, Miriam K.; Piedimonte, Giovanni (Frontiers in Immunology, 2022)
Overt and subclinical maternal infections in pregnancy can have multiple and significant pathological consequences for the developing fetus, leading to acute perinatal complications and/or chronic disease throughout postnatal life. In this context, the current concept of pregnancy as a state of systemic immunosuppression seems oversimplified and outdated. Undoubtedly, in pregnancy the maternal immune system undergoes complex changes to establish and maintain tolerance to the fetus while still protecting from pathogens. In addition to downregulated maternal immunity, hormonal changes, and mechanical adaptation (e.g., restricted lung expansion) make the pregnant woman more susceptible to respiratory pathogens, such as influenza virus, respiratory syncytial virus (RSV), and severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Depending on the infectious agent and timing of the infection during gestation, fetal pathology can range from mild to severe, and even fatal. Influenza is associated with a higher risk of morbidity and mortality in pregnant women than in the general population, and, especially during the third trimester of pregnancy, mothers are at increased risk of hospitalization for acute cardiopulmonary illness, while their babies show higher risk of complications such as prematurity, respiratory and neurological illness, congenital anomalies, and admission to neonatal intensive care. RSV exposure in utero is associated with selective immune deficit, remodeling of cholinergic innervation in the developing respiratory tract, and abnormal airway smooth muscle contractility, which may predispose to postnatal airway inflammation and hyperreactivity, as well as development of chronic airway dysfunction in childhood. Although there is still limited evidence supporting the occurrence of vertical transmission of SARS-CoV-2, the high prevalence of prematurity among pregnant women infected by SARS-CoV-2 suggests this virus may alter immune responses at the maternal-fetal interface, affecting both the mother and her fetus. This review aims at summarizing the current evidence about the short- and long-term consequences of intrauterine exposure to influenza, RSV, and SARS-CoV-2 in terms of neonatal and pediatric outcomes.